1993
DOI: 10.1007/bf01465873
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experimental study of a transferred arc stabilized with argon and flowing in a controlled-atmosphere chamber filled with argon at atmospheric pressure

Abstract: For a Iran.sJbrred arc with ~1 /7~11 (ltlodc working at tlD~tosl~]l¢'ri (' pr(,ssltrc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…If now N-1 nozzle is considered, it can be observed that the effect of the flow rate is essentially reversed, since higher energy transfer rates to the anode are associated with the lower sheath gas flow rates.. A similar negative trend for a cylindrical nozzle has been reported in by the Limoges group in 1993 [12]. The reason provided by [12] to explain this behaviour is that a recirculation flow pattern exists in the cathodic region, which becomes stronger with increasing flow rates and consequently leads to the lower jet velocities and temperatures existing in the anodic region.…”
Section: Calorimetric Measurementssupporting
confidence: 62%
See 2 more Smart Citations
“…If now N-1 nozzle is considered, it can be observed that the effect of the flow rate is essentially reversed, since higher energy transfer rates to the anode are associated with the lower sheath gas flow rates.. A similar negative trend for a cylindrical nozzle has been reported in by the Limoges group in 1993 [12]. The reason provided by [12] to explain this behaviour is that a recirculation flow pattern exists in the cathodic region, which becomes stronger with increasing flow rates and consequently leads to the lower jet velocities and temperatures existing in the anodic region.…”
Section: Calorimetric Measurementssupporting
confidence: 62%
“…The reason provided by [12] to explain this behaviour is that a recirculation flow pattern exists in the cathodic region, which becomes stronger with increasing flow rates and consequently leads to the lower jet velocities and temperatures existing in the anodic region. However, by using the appropriate boundary conditions at the cathode wall for the solution of Eqs.…”
Section: Calorimetric Measurementsmentioning
confidence: 90%
See 1 more Smart Citation
“…Paik et al 21 calculated the effect of working gas on the thermal profile of the arc in a 5 kW power supply waste treatment furnace. Coudert et al 22 studied the heat loss at the anode for an argon arc for a current up to 300 A. Mckelliget and Szekely 23 formulated a model to calculate the heat transfer to anode for the welding arc having a current from 100 to 200 A. Alexis et al 24 have calculated the heat flux, temperature, velocities and shear stress on anode surface for 36 kA current and 15-30 cm arc length. Taking this input as boundary conditions, Ramirez et al 25 studied the mixing in the bath.…”
Section: Introductionmentioning
confidence: 99%
“…Transferred arc plasma is widely used technology for melting and vitrification of hazardous wastes due to its high temperatures and simplicity of generation and control. The transferred arc plasma is assumed to be stable, steady, axi-symmetric, optically thin and in a local thermodynamic equilibrium (LTE) in an atmospheric-pressure environment [7,8]. The process is characterized by extremely high temperatures (up to 20,000-30,000 K), excellent arc stability and low environmental impact (low oxides emissions, low percentage of ultra-fine powder).…”
mentioning
confidence: 99%